Preferred vs Actual Hours in Couple Households - Wooden, M; Tseng, Y (My University, 2005)
Working hours in Australia are quite widely distributed around the population mean. That is, there are relatively many people working both relatively short hours and relatively long hours each week. From a welfare perspective, however, it is not the actual number of hours worked that is of importance, but whether the hours being worked are consistent with individual preferences. In this paper the question of how closely hours preferences are being met is examined using data collected in the first wave of the HILDA Survey. The study focuses specifically on workers in couple households. The analysis involved two main stages. In the first stage, evidence of a significant time divide – the co-existence of many people working part-time hours who would prefer to work longer and many people working very long hours who ould prefer to work fewer hours – is found. The extent of this time divide, however, should not be overstated – the hours of the majority of workers are still reasonably close to their stated preference. The second stage of the analysis focused on identifying the factors associated with mismatch in working hours preferences. The extent of overemployment, for example, is found to rise with age, and is more pronounced among the self-employed and less pronounced among those with a recent history of unemployment. Underemployment, on the other hand, is also associated positively with self-employment, as well as with casual employment. Perhaps of most interest, we find that in couples preferred hours are influenced by whether or not, and the extent to which, partners achieve their working time preferences. That is, if one member of the couple is unable to work as many hours as desired, this leads their partner to prefer more hours.
Melbourne Institute of Applied Economic and Social Research Working Paper Series
Keywords: Employment; Employment -- Hours; Labour market; Employment and unemployment